Reference electrode material and preparation method and application thereof

By coating the lithium-ion battery reference electrode material with a porous polymer coating with high porosity and high specific surface area, the problems of insufficient stability and service life of the lithium-ion battery reference electrode are solved, and high-precision potential testing and stability improvement are achieved.

CN120834310APending Publication Date: 2025-10-24三一红象电池有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510994945.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2025-10-24

AI Technical Summary

Technical Problem

Existing lithium-ion battery reference electrodes require a separator during battery fabrication, and their stability and lifespan are insufficient, leading to inaccurate test potential results.

Method used

A non-conductive coating is coated onto a conductive substrate. The non-conductive coating is composed of a porous polymer material, which is prepared by reacting a benzene ring-containing aromatic monomer and dimethoxymethane under Lewis acid catalysis to form a hypercrosslinked porous polymer with high porosity and high specific surface area, which serves as a reference electrode material.

Benefits of technology

It can reduce concentration polarization without the need for an additional diaphragm, improve test accuracy, extend the stable lifespan of the reference electrode, and simplify the packaging of three electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120834310A_ABST
    Figure CN120834310A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and particularly relates to a reference electrode material and a preparation method and application thereof. The reference electrode material provided by the invention comprises a conductive base material and a non-conductive coating, the non-conductive coating is coated on the conductive base material; the non-conductive coating comprises a porous polymer material; the porous polymer material is obtained by reacting a benzene ring-containing aromatic monomer and dimethoxymethane under the catalysis of Lewis acid. When the reference electrode material is used for preparing a lithium battery, an additional diaphragm is not needed, concentration polarization can be effectively reduced, the test potential deviation is small, the accuracy is high, and meanwhile, the reference electrode material is stable, stable and long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of battery materials, and particularly relates to a reference electrode material and a preparation method and application thereof. BACKGROUND

[0002] The lithium ion battery three-electrode technology has become a mature method for cell system development and failure analysis, such as lithium extraction window detection, full impedance decomposition and positive and negative electrode charging and discharging behavior. However, the existing three-electrode technology needs to introduce multiple diaphragms, which greatly increases the concentration polarization between the reference electrode and the counter electrode, causing the test potential result to be distorted from the actual value; and the existing technical solution has the disadvantage of poor stability of the lithium-plated reference electrode, which is difficult to monitor the long-term cycle potential change.

[0003] The existing technology mainly includes a metal wire electrochemical lithium plating method, an embedded metal lithium sheet method and a foam copper-molten lithium method, etc. The metal wire electrochemical lithium plating method is the most simple to operate, and is a widely used lithium ion battery three-electrode reference preparation method. The specific technical details include that the metal wire is embedded in the cell after being etched by concentrated acid, and a dense layer of lithium metal is deposited on the surface of the metal wire by electrochemical deposition, thereby obtaining a lithium reference electrode with constant potential. However, the existing lithium ion battery reference electrode needs a diaphragm in the preparation of the battery, and the stability and stable service life of the lithium ion battery reference electrode still need to be improved. SUMMARY

[0004] Therefore, the technical problem to be solved by the present application is to overcome the defects that the existing lithium ion battery reference electrode needs a diaphragm in the preparation of the battery, and the stability and stable service life of the lithium ion battery reference electrode still need to be improved, so as to provide a reference electrode material and a preparation method and application thereof.

[0005] The present application provides a reference electrode material, which comprises a conductive substrate and a non-conductive coating.

[0006] The non-conductive coating is coated on the conductive substrate.

[0007] The non-conductive coating comprises a porous polymer material.

[0008] The porous polymer material is obtained by reacting a benzene ring-containing aromatic monomer and dimethoxymethane under the catalysis of a Lewis acid.

[0009] Preferably, the specific surface area of the porous polymer material is 500-2000 m 2 g -1 The average pore size of the porous polymer material is 1-3 nm.

[0010] And / or, the benzene ring-containing aromatic monomer is selected from at least one of benzene, biphenyl, triphenylbenzene, triplytene;

[0011] And / or, the Lewis acid is selected from at least one of AlCl3, FeCl3, SnCl4 or ZnCl2;

[0012] And / or, the non-conductive coating has a thickness of 1-20 microns.

[0013] The Lewis acid used in the present application is all anhydrous Lewis acid, such as anhydrous AlCl3, anhydrous FeCl3, anhydrous SnCl4 or anhydrous ZnCl2.

[0014] Preferably, the molar ratio of the benzene ring-containing aromatic monomer to the dimethoxymethane is (0.1-2):1;

[0015] And / or, the molar ratio of the Lewis acid to the dimethoxymethane is (0.5-2):1;

[0016] And / or, the reaction temperature is 40-100℃, and the reaction time is 0.5-12h;

[0017] And / or, the reaction is carried out in an organic solvent selected from at least one of dichloromethane, dichloroethane, dibromomethane, dibromoethane;

[0018] Optionally, the mass concentration of the benzene ring-containing aromatic monomer in the organic solvent is 10-50mg / mL.

[0019] Optionally, the reaction further comprises a washing step after the reaction.

[0020] Preferably, the non-conductive coating comprises a porous polymer material and a binder;

[0021] Preferably, the non-conductive coating comprises 70%-98% of the porous polymer material and 2%-30% of the binder by mass percentage;

[0022] The binder comprises at least one of polyvinylidene fluoride (PVDF), styrene-butadiene rubber, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylonitrile, and polyacrylic acid;

[0023] Preferably, the binder is selected from at least one of polyvinylidene fluoride (PVDF) and styrene-butadiene rubber (SBR).

[0024] Preferably, the conductive substrate comprises at least one of a metal wire, a carbon fiber, and an enameled metal wire;

[0025] The metal wire comprises at least one of a copper wire, a platinum wire, and a silver wire;

[0026] The enameled metal wire comprises at least one of enameled copper wire, enameled silver wire and enameled platinum wire.

[0027] Preferably, the diameter of the conductive substrate is 10-200 μm.

[0028] The present application provides a preparation method of the reference electrode material, comprising the following steps:

[0029] The exposed end of the conductive substrate is immersed in the non-conductive slurry, and after the immersion is completed, drying is performed to obtain the reference electrode material with the non-conductive coating covering one end.

[0030] Preferably, the solvent in the non-conductive slurry is at least one of N,N-dimethylformamide, N-methyl-2-pyrrolidone (NMP) and N,N-dimethylacetamide.

[0031] The solid content of the non-conductive slurry is 3%-30%.

[0032] The solid content of the non-conductive coating slurry is the total mass content of the components other than the solvent in the non-conductive coating slurry, and the solid content of the non-conductive coating slurry is the total mass content of the porous polymer material and the binder in the non-conductive coating slurry.

[0033] Preferably, the immersion time is 5-30 s.

[0034] In addition, before the exposed end of the conductive substrate is immersed in the non-conductive slurry, the exposed end of the conductive substrate is wetted with the solvent in the non-conductive slurry.

[0035] Wetting can reduce the surface tension of the metal during the coating process, thereby preventing material leakage (i.e., preventing the non-conductive slurry from not being coated in some positions). For example, when the solvent of the non-conductive slurry is N-methyl-2-pyrrolidone, before the exposed end of the conductive substrate is immersed in the non-conductive slurry, the exposed end of the conductive substrate is wetted with N-methyl-2-pyrrolidone.

[0036] Preferably, the exposed end of the conductive substrate is an end where the conductive material is exposed.

[0037] Optionally, both ends of the carbon fiber are exposed ends, and both ends of the metal wire are exposed ends.

[0038] Optionally, the enameled metal wire is pretreated to form the exposed end.

[0039] Optionally, the pretreatment comprises placing both ends of the enameled metal wire in a sulfuric acid solution for 10-120 min to remove the surface enameled layer, 0.5-3 cm of one end and 3-7 cm of the other end, to obtain the exposed end.

[0040] Optionally, the exposed end of the conductive substrate further comprises a step of cleaning it with deionized water or ethanol before use.

[0041] Optionally, the mass concentration of sulfuric acid in the sulfuric acid solution is 20% to 98%.

[0042] The application provides a lithium ion battery comprising the reference electrode material or the reference electrode material prepared by the preparation method.

[0043] The one end of the reference electrode material coated with the non-conductive coating is placed in the middle of the soft package battery core, without adding an additional separator, and a three-electrode soft package lithium battery is prepared with a positive electrode and a negative electrode, and then the reference electrode material is plated with lithium, the step of plating the reference electrode material with lithium comprising: connecting the external positive electrode power line to the positive electrode tab of the three-electrode core, connecting the external negative electrode power line to the reference electrode material, and plating lithium at 10-30 mu A for 1-2 hours and plating lithium at 3-8 mu A for 1-3 hours; then connecting the external positive electrode power line to the negative electrode tab of the three-electrode core, and still connecting the external negative electrode power line to the reference electrode material, and using the same lithium plating method as the positive electrode side, and finally obtaining the reference electrode with a uniform and dense lithium plating layer.

[0044] Optionally, the middle of the core comprises the middle of the core in the thickness direction, the middle of the core in the length direction and the middle of the core in the width direction, the exposed end (3-7 cm) of the metal wire / enameled metal wire is led out of the shell, and the external tab is connected.

[0045] Optionally, the one end of the reference electrode material coated with the non-conductive coating is placed in the middle of the soft package lithium battery core, without adding an additional separator, and a three-electrode soft package battery is obtained after packaging, baking, liquid injection, formation and capacity distribution of the positive electrode and the negative electrode.

[0046] Optionally, the positive electrode of the three-electrode soft package lithium battery is lithium iron phosphate, and the negative electrode is graphite.

[0047] The technical scheme of the application has the following advantages:

[0048] 1. The reference electrode material provided by the application, wherein, the reference electrode material comprises a conductive substrate and a non-conductive coating layer; the non-conductive coating layer is coated on the conductive substrate; the non-conductive coating layer comprises a porous polymer material; the porous polymer material is obtained by the reaction of a benzene ring-containing aromatic monomer and dimethoxymethane under the catalysis of a Lewis acid. The reaction of the benzene ring-containing aromatic monomer and dimethoxymethane under the catalysis of the Lewis acid obtains a hypercrosslinked porous polymer with high porosity and high specific surface area. The lithium ion battery reference electrode material provided by the application is prepared by coating a layer of non-conductive, hypercrosslinked porous polymer with high porosity and high specific surface area on the conductive substrate. The porous polymer material can construct an electron insulation layer on the surface of the composite reference electrode material, play a diaphragm role, and prevent the reference electrode material from contacting the positive electrode or the negative electrode to cause short circuit; the high porosity or specific surface area characteristics can construct a Li + The transmission path is increased, and the electrolyte retention amount is increased. When the reference electrode material provided by the application is used to prepare a lithium battery, no additional diaphragm is needed, the concentration polarization can be effectively reduced, the test potential deviation is small, the precision is high, the reference electrode material is stable, and the service life is long.

[0049] 2. The reference electrode material provided by the application, wherein, the benzene ring-containing aromatic monomer used to prepare the porous polymer material is at least one selected from the group consisting of benzene, biphenyl, triphenylbenzene and triptycene; the pore structure of the obtained hypercrosslinked porous polymer can be adjusted by optimizing the chemical structure of the monomer, and when the reference electrode material is plated with lithium, the Li + The non-conductive porous insulation layer formed by the porous polymer is first passed through, lithium metal is deposited after reaching the substrate, and finally a lithium metal composite reference electrode is formed. When the reference electrode material provided by the application is used to prepare a lithium battery, no additional diaphragm is needed, the concentration polarization can be further effectively reduced, the test precision is high, the reference electrode material is more stable, and the service life is higher.

[0050] 3. The reference electrode material provided by the application, wherein, when the lithium battery is prepared, no additional diaphragm is needed, and the three-electrode packaging difficulty is greatly reduced. DETAILED DESCRIPTION

[0051] In order to more clearly illustrate the specific embodiments of the present application or the technical solutions in the prior art, the drawings needed in the specific embodiments or the prior art description will be briefly introduced below. Obviously, the drawings in the following description are some embodiments of the present application, and those skilled in the art can also obtain other drawings according to these drawings without creating any creative labor.

[0052] Figure 1 The negative electrode-reference potential diagram of the lithium iron phosphate / graphite three-electrode battery prepared by the reference electrode material of the embodiment 1 after 300h of cycle;

[0053] Figure 2 The difference between the lowest negative reference potential of each cycle and the lowest negative reference potential of the first cycle of the lithium iron phosphate / graphite three-electrode battery prepared from the reference electrode material of Example 1, Example 2 and Comparative Example 1 is shown in the following chart:

[0054] Figure 3 The negative reference potential of the fifth cycle of the lithium iron phosphate / graphite three-electrode battery prepared from the reference electrode material of Example 1 and Comparative Example 3 is shown in the following chart. DETAILED DESCRIPTION

[0055] The following examples are provided to better further understand the present application and are not limited to the best mode contemplated, do not constitute limitations on the scope of the application and protection range thereof, and any product identical or similar to the present application obtained by the inspiration of the present application or by combining the present application with other prior art features falls within the protection scope of the present application.

[0056] The specific experimental steps or conditions not mentioned in the examples can be performed according to the conventional experimental steps described in the literature in the art or the operation or conditions. The reagents or instruments not mentioned by the manufacturer are conventional reagent products that can be obtained by market purchase.

[0057] Example 1

[0058] The present embodiment provides a preparation method of a reference electrode material, which comprises the following steps:

[0059] 0.78g of benzene was dissolved in 20mL of dichloroethane at room temperature, and after being stirred uniformly, 0.76g of dimethoxymethane and 1.62g of anhydrous ferric chloride were added, and the temperature was slowly increased to 80℃ for 6h of reaction. After the reaction was completed, the obtained crude product was washed with deionized water for 7 times in sequence to remove residual organic solvents and catalysts, and finally dried at 80℃ to obtain a tan porous polymer A; the BET specific surface area of the porous polymer A was 1260m 2 g -1 , mainly microporous and mesoporous, containing a small amount of macroporous, and the average pore size was 2.5nm;

[0060] A section of 15cm, 50μm in diameter, of enameled copper wire was taken as a substrate, and one end of 3cm and one end of 5cm were immersed in concentrated sulfuric acid with a mass concentration of 98% for 60min to remove the enamel, and then washed with deionized water for 10min, and after being washed clean, the enameled copper wire with two ends exposed was dried to obtain;

[0061] According to the mass fraction ratio of porous polymer A: binder (PVDF) = 80wt%: 20wt%, porous polymer A and PVDF were weighed and dissolved in NMP solvent, and after being fully stirred uniformly, a non-conductive slurry was obtained, and the solid content was 20%;

[0062] The 3cm exposed end of the enameled copper wire was wetted with NMP, then immersed in the non-conductive slurry for 15s, so that the exposed end of the enameled copper wire was completely coated with the non-conductive slurry. After natural air drying, the reference electrode material with one end coated with a non-conductive coating and a bare length of 5cm was obtained. The non-conductive coating thickness was about 8μm.

[0063] Example 2

[0064] The present embodiment provides a preparation method of a reference electrode material, comprising the following steps:

[0065] 0.77g of biphenyl was dissolved in 20mL of dichloroethane at room temperature, and after stirring uniformly, 0.76g of dimethoxymethane and 1.62g of anhydrous ferric chloride were added. Slowly heated to 80℃ for 6h. After the reaction was completed, the crude product was washed with deionized water for 7 times in sequence to remove residual organic solvents and catalysts. Finally, dried at 80℃ to obtain porous polymer B; the BET specific surface area of the porous polymer B was 775m 2 g -1 , mainly microporous and mesoporous, containing a small amount of macroporous, with an average pore size of 1.7nm;

[0066] A 15cm long enameled copper wire with a diameter of 50μm was cut as a substrate. Its one end was 3cm long and the other end was 5cm long. The paint was removed by immersing it in concentrated sulfuric acid with a mass concentration of 98% for 60min. Then it was washed with deionized water for 10min. After cleaning and drying, the enameled copper wire with both ends exposed was obtained;

[0067] According to the mass fraction ratio of porous polymer B: binder (PVDF) = 80wt%: 20wt%, porous polymer B and PVDF were weighed and dissolved in NMP solvent. After stirring uniformly, a non-conductive slurry was obtained, with a solid content of 20%.

[0068] The 3cm exposed end of the enameled copper wire was wetted with NMP, then immersed in the non-conductive slurry for 15s, so that the exposed end of the enameled copper wire was completely coated with the non-conductive slurry. After natural air drying, the reference electrode material with one end coated with a non-conductive coating and a bare length of 5cm was obtained. The non-conductive coating thickness was about 8μm.

[0069] Example 3

[0070] The present embodiment provides a preparation method of a reference electrode material, comprising the following steps:

[0071] 0.298 g of triptycene was dissolved in 20 mL of dichloroethane at room temperature, 0.76 g of dimethoxymethane and 1.62 g of anhydrous ferric chloride were added after stirring uniformly, and the temperature was slowly increased to 80°C for 6 h. After the reaction was completed, the obtained crude product was washed with deionized water for 7 times in sequence, and the residual organic solvent and catalyst were removed, and finally dried at 80°C to obtain a porous polymer C; the BET specific surface area of the porous polymer C was 1945 m 2 g -1 The obtained product was mainly microporous and mesoporous, containing a small amount of macroporous, and the average pore size was 2.2 nm;

[0072] A 15 cm long, 50 μm diameter enameled copper wire was taken as a substrate, and its one end with a length of 3 cm and the other end with a length of 5 cm were immersed in concentrated sulfuric acid with a mass concentration of 98% for 60 min to remove the enamel, and then washed with deionized water for 10 min. After being washed clean, the enameled copper wire with bare ends was dried to obtain a reference electrode material with one end coated with a non-conductive coating and a bare length of 5 cm.

[0073] The porous polymer C and PVDF were weighed according to the mass fraction ratio of 80 wt%:20 wt%, and dissolved in NMP solvent to obtain a non-conductive slurry after being stirred uniformly, and the solid content was 20%.

[0074] The 3 cm long bare end of the enameled copper wire was wetted with NMP, and then immersed in the non-conductive slurry for 15 s to completely coat the bare end of the enameled copper wire with the non-conductive slurry. After being naturally dried, the reference electrode material with one end coated with a non-conductive coating and a bare length of 5 cm was obtained, and the thickness of the non-conductive coating was about 9 μm.

[0075] Example 4

[0076] The difference between the reference electrode preparation method of this embodiment and that of Example 1 is that the “PVDF” is replaced by “styrene butadiene rubber (SBR)”.

[0077] Example 5

[0078] The reference electrode material preparation method of this embodiment comprises the following steps:

[0079] 0.78 g of benzene was dissolved in 20 mL of dichloroethane at room temperature, 0.76 g of dimethoxymethane and 1.62 g of anhydrous ferric chloride were added after stirring uniformly, and the temperature was slowly increased to 80°C for 6 h. After the reaction was completed, the obtained crude product was washed with deionized water for 7 times in sequence, and the residual organic solvent and catalyst were removed, and finally dried at 80°C to obtain a yellowish-brown porous polymer A; the BET specific surface area of the porous polymer A was 1260 m 2 g -1 It was mainly microporous and mesoporous, containing a small amount of macroporous, and the average pore size was 2.5 nm.

[0080] A 15 cm long, 50 μm diameter enameled copper wire was taken as a substrate, and its one end with a length of 3 cm and the other end with a length of 5 cm were sequentially immersed in concentrated sulfuric acid with a mass concentration of 98% for 60 min to remove the enamel, and then washed with deionized water for 10 min. After being washed clean, the enameled copper wire was dried to obtain a bare enameled copper wire with both ends bare.

[0081] The porous polymer A and PVDF were weighed according to a mass fraction ratio of porous polymer A: binder (PVDF) = 70 wt%: 30 wt%, dissolved in NMP solvent, and uniformly stirred to obtain a non-conductive slurry with a solid content of 30%;

[0082] The 3 cm long bare end of the enameled copper wire was wetted with NMP, and then immersed in the non-conductive slurry for 25 s to completely coat the bare end of the enameled copper wire with the non-conductive slurry. After being naturally dried, the reference electrode material with one end coated with a non-conductive coating and a bare length of 5 cm was obtained. The non-conductive coating had a thickness of about 13 μm after being measured.

[0083] Example 6

[0084] The present example provides a method for preparing a reference electrode material, which comprises the following steps:

[0085] At room temperature, 0.78 g of benzene was dissolved in 20 mL of dichloroethane, and then 0.76 g of dimethoxymethane and 1.62 g of anhydrous ferric chloride were added after being uniformly stirred. The mixture was slowly warmed to 80 °C and reacted for 6 h. After the reaction was completed, the obtained crude product was sequentially washed with deionized water for 7 times to remove residual organic solvents and catalysts, and finally dried at 80 °C to obtain a yellowish-brown porous polymer A. The BET specific surface area of the porous polymer A was 1260 m 2 g -1 , which was mainly microporous and mesoporous, contained a small amount of macropores, and had an average pore size of 2.5 nm.

[0086] A 15 cm long, 50 μm diameter enameled copper wire was taken as a substrate, and its one end with a length of 3 cm and the other end with a length of 5 cm were sequentially immersed in concentrated sulfuric acid with a mass concentration of 98% for 60 min to remove the enamel, and then washed with deionized water for 10 min. After being washed clean, the enameled copper wire was dried to obtain a bare enameled copper wire with both ends bare.

[0087] The porous polymer A and PVDF were weighed according to a mass fraction ratio of porous polymer A: binder (PVDF) = 90 wt%: 10 wt%, dissolved in NMP solvent, and uniformly stirred to obtain a non-conductive slurry with a solid content of 15%;

[0088] The 3cm exposed end of the enameled copper wire was wetted with NMP, then immersed in the non-conductive slurry for 10S, so that the exposed end of the enameled copper wire was completely coated with the non-conductive slurry, and after natural air drying, the reference electrode material with one end coated with a non-conductive coating and a bare length of 5cm was obtained. The non-conductive coating thickness was about 7μm after measurement.

[0089] Comparative Example 1

[0090] The present comparative example provides a preparation method of a reference electrode material, comprising the following steps:

[0091] A 15cm long enameled copper wire with a diameter of 50μm was cut as a substrate, and its one end with a length of 3cm and the other end with a length of 5cm were sequentially immersed in concentrated sulfuric acid with a mass concentration of 98% for 60min to remove the enamel, then washed with deionized water for 10min, and after cleaning and drying, the enameled copper wire with both ends exposed was obtained. The 3cm exposed end of the enameled copper wire was used as a reference electrode material.

[0092] Comparative Example 2

[0093] The present comparative example provides a preparation method of a reference electrode material, comprising the following steps:

[0094] A 15cm long enameled copper wire with a diameter of 50μm was cut as a substrate, and its one end with a length of 3cm and the other end with a length of 5cm were sequentially immersed in concentrated sulfuric acid with a diameter of 50μm was cut as a substrate, and its one end with a length of 3cm and the other end with a length of 5cm were sequentially immersed in concentrated sulfuric acid with a mass concentration of 98% for 60min to remove the enamel, then washed with deionized water for 10min, and after cleaning and drying, the enameled copper wire with both ends exposed was obtained. The 3cm exposed end of the enameled copper wire was used as a reference electrode material.

[0095] Silicon dioxide and PVDF were weighed according to the mass fraction ratio of silicon dioxide: binder (PVDF) = 80wt%:20wt%, dissolved in NMP solvent, and after uniform stirring, a non-conductive slurry was obtained, with a solid content of 20%;

[0096] The 3cm exposed end of the enameled copper wire was wetted with NMP, then immersed in the non-conductive slurry for 10S, so that the exposed end of the enameled copper wire was completely coated with the non-conductive slurry, and after natural air drying, the reference electrode material with one end coated with a non-conductive coating and a bare length of 5cm was obtained. The non-conductive coating thickness was about 7μm after measurement.

[0097] Comparative Example 3

[0098] The present comparative example provides a reference electrode material, comprising the following steps:

[0099] 30wt% of polyethylene oxide, 15wt% of lithium bis-trifluoromethylsulfonylimide, 5wt% of aluminum sesquioxide, and 50wt% of diethyl carbonate were put into a magnetic stirrer, then magnetic stirring was performed, and defoaming treatment was performed to obtain a solid-state electrolyte slurry;

[0100] A length of about 15 cm, 50 μm in diameter, enameled copper wire was taken as a substrate, one end of which was about 3 cm long and the other end was about 5 cm long. The two ends were immersed in dilute hydrochloric acid for 60 min and deionized water for 10 min, respectively, and then cleaned and dried to obtain enameled copper wire with two bare ends;

[0101] According to the mass fraction ratio of solid electrolyte slurry: binder (PVDF) = 80wt%: 20wt%, solid electrolyte slurry and PVDF were weighed and dissolved in NMP solvent, and then uniformly stirred to obtain a non-conductive slurry with a solid content of 20%.

[0102] The 3 cm bare end of the enameled copper wire was wetted with NMP and then immersed in the non-conductive slurry for 15 s, so that the bare end of the enameled copper wire was completely coated with the non-conductive slurry. After natural drying, the reference electrode material with one end coated with a non-conductive coating and a bare length of 5 cm was obtained.

[0103] Test Example

[0104] One end of the reference electrode material coated with a non-conductive coating prepared in Examples 1-6 and Comparative Examples 2-3 of the present application was placed in the middle of the length direction of the soft pack battery core without adding an additional separator. The positive electrode of the soft pack battery was lithium iron phosphate, and the negative electrode was graphite. The bare end (5 cm bare end) of the reference electrode material was led out of the shell and connected to the tab to form a reference electrode tab. After preparing the three-electrode soft pack battery, the reference electrode material was plated with lithium. The plating step was as follows: the external positive power line was connected to the three-electrode core positive tab, the external negative power line was connected to the reference electrode tab, 20 μA plating for 1.5 h, and then 5 μA plating for 2 h. Then the external positive power line was connected to the three-electrode core negative tab, and the external negative power line was still connected to the reference electrode tab. The lithium metal composite reference electrode was obtained by plating at 20 μA for 1.5 h and then at 5 μA for 2 h. At the same time, a three-electrode lithium battery containing the lithium metal composite reference electrode was also obtained.

[0105] The 3 cm bare end of the reference electrode material of the inventive comparative example 1 was placed in the middle of the soft pack battery core length direction, the reference electrode material was between the positive electrode and the negative electrode, and a separator was arranged between the reference electrode material and the positive electrode and between the reference electrode material and the negative electrode. The positive electrode of the soft pack battery was lithium iron phosphate, the negative electrode was graphite, and the separator material was polypropylene (PP). The bare end (5 cm bare end) of the reference electrode material was led out of the shell, and the reference electrode tab was formed by connecting the external tab. After the three-electrode soft pack battery was prepared, the reference electrode material was plated with lithium. The plating step was as follows: the external positive electrode power line was connected to the three-electrode core positive tab, the external negative electrode power line was connected to the reference electrode tab, 20 μA plating for 1.5 h, then 5 μA plating for 2 h; then the external positive electrode power line was connected to the three-electrode core negative tab, and the external negative electrode power line was still connected to the reference electrode tab, 20 μA plating for 1.5 h, then 5 μA plating for 2 h, to obtain a lithium metal composite reference electrode. A three-electrode lithium battery containing the lithium metal composite reference electrode was also obtained.

[0106] The three-electrode lithium batteries containing the lithium metal composite reference electrode prepared from the reference electrode materials of examples 1-6 and comparative examples 1-3 above were subjected to electrochemical performance testing in a 25℃ environment. The voltage range was 2.5-3.65 V, and the charge-discharge test was carried out on a blue electrochemical workstation using equivalent 0.8C (1C CC 80% SOC, 0.6C CC 92% SOC, 0.4C CC 3.5V, 0.1C CC 3.65V, wherein CC represents constant current charging, and SOC represents the percentage of the current capacity to the total capacity). The charge-discharge ended, and the standing time was 30 min, respectively. One complete cycle was 197 min, and a total of 200 cycles were counted. The electrode potential change was monitored. As the reference electrode potential, the negative electrode potential, and the positive electrode potential could be measured in the first cycle, the three-electrode potential could be successfully detected, and the test results are shown in Table 1. The stability (potential fluctuation amplitude) of the reference electrode materials prepared from examples 1-6 and comparative examples 1-3 of the present application was evaluated, and the stable test duration was recorded. The stability evaluation standard was as follows: the difference between the lowest potential of the negative electrode relative to the reference electrode (negative electrode-reference potential) in any 2 cycles within 10 h was ≤10 mV, which was considered as stable reference electrode; the difference between the lowest potential of the negative electrode relative to the reference electrode (negative electrode-reference potential) in any 2 cycles within 10 h was >10 mV, which was considered as poor stability of the reference electrode, and the test results are shown in Table 1. The lowest negative electrode-reference potential of each cycle was recorded, and the drift difference value of the lowest negative electrode-reference potential of the first cycle was recorded. The drift difference value of the lowest negative electrode-reference potential of the first cycle relative to the lowest negative electrode-reference potential of the first cycle in the first 31 cycles (about 100 h) and the first 92 cycles (about 300 h) is shown in Table 1. The negative electrode-reference potential graph of the lithium iron phosphate / graphite three-electrode battery prepared from the reference electrode material of example 1 cycled for 300 h is shown in FIG. 1.Figure 1 Figure 4 is a graph showing the difference between the lowest negative- reference potential of each cycle and the lowest negative- reference potential of the first cycle of the lithium iron phosphate / graphite three-electrode battery prepared using the reference electrode material of Example 1, 2 and Comparative Example 1. Figure 2 Figure 5 is a graph showing the negative- reference potential of the fifth cycle of the lithium iron phosphate / graphite three-electrode battery prepared using the reference electrode material of Example 1 and Comparative Example 3. Figure 3

[0107] Table 1

[0108]

[0109]

[0110] Note: - represents a decrease in the difference between the lowest negative- reference potential of each cycle and the lowest negative- reference potential of the first cycle, / represents a rapid increase in the decrease in the difference between the lowest negative- reference potential of each cycle and the lowest negative- reference potential of the first cycle, reaching more than -25 mV, and subsequent testing is meaningless, i.e., no testing is performed.

[0111] A small concentration polarization means that the lowest potential will be higher, closer to the true negative potential. When evaluating the charge capacity of a battery, a battery with large concentration polarization will be misled by the test data, resulting in an underestimated electrochemical performance. From Figure 3 It can be seen that the reference electrode of Example 1 of the present application has small concentration polarization (the lowest negative- reference potential of the battery is > 0 mV at this time, and is further away from 0 mV than Comparative Example 1).

[0112] Obviously, the above examples are merely examples for the sake of clarity, and are not limiting of the embodiments. For those of ordinary skill in the art, other different forms of changes or variations can be made on the basis of the above description. It is not necessary or possible to exhaust all embodiments. The obvious changes or variations derived therefrom are still within the protection scope of the present application.​

Claims

1. A reference electrode material, characterized in that, The reference electrode material comprises a conductive substrate and a non-conductive coating layer; The non-conductive coating layer is coated on the conductive substrate; The non-conductive coating layer comprises a porous polymer material; The porous polymer material is obtained by reacting a benzene ring-containing aromatic monomer and dimethoxymethane under the catalysis of a Lewis acid.

2. The reference electrode material of claim 1, wherein, The specific surface area of the porous polymer material is 500-2000 m 2 g -1 The average pore diameter of the porous polymer material is 1-3 nm. And / or, the benzene ring-containing aromatic monomer is selected from at least one of benzene, biphenyl, triphenylbenzene, and triply. And / or, the Lewis acid is selected from at least one of AlCl3, FeCl3, SnCl4, or ZnCl2. And / or, the thickness of the non-conductive coating layer is 1-20 μm.

3. The reference electrode material according to claim 1 or 2, characterized in that, The molar ratio of the benzene ring-containing aromatic monomer to the dimethoxymethane is (0.1-2):

1. And / or, the molar ratio of the Lewis acid to the dimethoxymethane is (0.5-2):

1. And / or, the reaction temperature is 40-100°C, and the reaction time is 0.5-12 h. And / or, the reaction is carried out in an organic solvent selected from at least one of dichloromethane, dichloroethane, dibromomethane, and dibromoethane. Optionally, the mass concentration of the benzene ring-containing aromatic monomer in the organic solvent is 10-50 mg / mL.

4. The reference electrode material according to any one of claims 1 to 3, characterized in that, The non-conductive coating layer comprises a porous polymer material and a binder; Preferably, the non-conductive coating layer comprises, by mass percentage, 70-98% of the porous polymer material and 2-30% of the binder. The binder comprises at least one of polyvinylidene fluoride (PVDF), styrene-butadiene rubber, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylonitrile, and polyacrylic acid. Preferably, the binder is selected from at least one of polyvinylidene fluoride (PVDF) and styrene-butadiene rubber (SBR).

5. The reference electrode material according to any one of claims 1 to 4, characterized in that, The conductive substrate comprises at least one of a metal wire, a carbon fiber, and an enameled wire. The metal wire comprises at least one of a copper wire, a platinum wire, and a silver wire. The enameled wire comprises at least one of an enameled copper wire, an enameled silver wire, and an enameled platinum wire. Preferably, the diameter of the conductive substrate is 10-200 μm.

6. A method for producing the reference electrode material according to any one of claims 1 to 5, characterized in that The method comprises the following steps: immersing the exposed end of the conductive substrate in a non-conductive slurry, and drying after the immersion to obtain the reference electrode material with the non-conductive coating layer coated on one end.

7. The method of claim 6, wherein the reference electrode material is prepared by the steps of: The solvent in the non-conductive slurry is at least one of N,N-dimethylformamide, N-methyl-2-pyrrolidone (NMP), and N,N-dimethylacetamide. The solid content of the non-conductive slurry is 3-30%.

8. The method of producing a reference electrode material according to claim 6 or 7, characterized in that, The immersion time is 5-30 s. And / or, before immersing the exposed end of the conductive substrate in the non-conductive slurry, the method further comprises the step of wetting the exposed end of the conductive substrate with the solvent in the non-conductive slurry.

9. The method of producing a reference electrode material according to any one of claims 6 to 8, characterized in that, The exposed end of the conductive substrate is an end where the conductive material is exposed. Optionally, both ends of the carbon fiber are exposed ends, and both ends of the metal wire are exposed ends. Optionally, the enameled wire is pre-processed to form the exposed end. Optionally, the pre-processing comprises placing both ends of the enameled wire in a sulfuric acid solution for 10-120 min to remove the surface enameled layer, 0.5-3 cm on one end and 3-7 cm on the other end, to obtain the exposed end. Optionally, the exposed end of the conductive substrate further comprises a step of washing it with deionized water or ethanol before use.

10. A lithium-ion battery, characterized by, The lithium ion battery comprises the reference electrode material according to any one of claims 1-5 or the reference electrode material prepared by the preparation method according to any one of claims 6-9.